Revisiting Money Demand In Malaysia: Simple-Sum Versus Divisia Monetary Aggregates - Puah, Chin Hong; Leong, Choi Meng; Shazali, Abu Mansor; Lau, Evan (2008)
This paper attempts to determine whether Divisia Monetary Aggregates is a superior monetary instrument in Malaysia where monetary targeting has been replaced by interest rate targeting due to the inadequacy of the monetary aggregates in predicting imperative economic activities. Is there any discernible evidence to suggest that Divisia monetary Aggregates possess significant relationship with the macroeconomics indicators? The empirical results in this study indicate that Divisia M2 performs excellently in the money demand function of Malaysia that incorporated the financial reform and financial development variables. The significance of Divisia money validates the usefulness of monetary targeting to formulate monetary policy in Malaysia.